A CASE STUDY IN THE DESIGN OF THE SAGE SENIOR CENTER AT INGERSOLL HOUSING IN NYC. (11th November 2018) - Porter, T
Abstract: Ted Porter Architecture's design of the SAGE Senior Center at Ingersoll Housing in NYC seeks to provide a welcoming space where older adults can enjoy services and programs related to arts and culture, food and nutrition, fitness, health and wellness, and lifelong education within a warm, inviting setting. SAGE is an organization dedicated to improving the lives of lesbian, gay, bisexual and transgender (LGBT) older adults, and while the new center will be open to anyone, its primary community will consist of LGBT older adults. The senior center will have flexible meeting rooms of varying sizes, a kitchen, a cyber center, and spaces for financial and legal consultations or other community services. Discussion will be focused on 1) how the needs of the community were integrated into the design, and 2) how safety, policy, and financial constraints may affect the implementation of design goals.